Concurrent presence of buccal mucosal and ophthalmologic lesions in Behcet's syndrome - Mojtaba Mikaniki; Neda Babaei; Ebrahim Mikaniki; Mohammadreza Hasanjaniroshan; Ali Bijani (Babol University of Medical Sciences, 2018)
Background: Behcet's syndrome is a disease with different aspects in its clinical manifestations. The purpose of this study was to evaluate the simultaneous presence of oral mucosal and ophthalmologic lesions in patients with Behcet's syndrome. Methods: From April 2012 to December 2014, 50 cases of Behcet's syndrome who referred to the Departments of Ophtalmology, Oral Diseases and Infectious Diseases of Babol University Medical Sciences were entered into the study. The diagnosis of the disease was performed using the Iranian criteria for the diagnosis of Behcet's syndrome.  The demographic findings as well as clinical manifestations were recorded. Results:  Thirt-six (72%) were males and 14 (28%) were females. The mean age of the patients was 35.6±9 years. Oral aphthous (94%), ocular lesion (76%) and genital ulcers (70%) were the most clinical findings. The clinical onset of the disease in 43 (86%) was oral lesions and in 5 (10%) was ocular lesions. Among the forty-eight cases with oral lesions, 77% had ocular lesions concurrently. HLA-B5 was positive in 35 (70%) cases. Ocular lesion was seen in 33 of 35 (91.4%) cases versus 6 of 15 (40%) with HLA-B5 positive and negative cases, respectively (p<0.05). Oral lesion was seen in 94.3% cases with positive HLA-B5 and in 100% cases with negative HLA-B5 (p>0.05). Conclusions: The results show that concurrent ophthalmic and oral lesions  in Behcet's syndrome are relatively high. HLA-B5 positive cases are associated with more ophthalmologic lesions.